Relationship Between Bone Mineral Density and Functional Parameters of Paraplegic Patients in Short-Term After Spinal Cord Injury-Original Investigation - Duygu Geler Külcü; Güliz Gönül; Binkan Sonel Tur; Yeşim Kurtaiş; Özlem Küçük; Duygu Geler Külcü (Galenos Yayinevi, 2008)
Aim: To determine the relationship between bone mineralization and functional activity level of paraplegic patients in short-term after spinal cord injury (SCI). Material and Methods: Thirty paraplegic patients and twentynine healthy controls were admitted to this study. Bone mineral density (BMD) and Z-scores, together with serum calcium, phosphorus, alkaline phosphatase, parathyroid hormone and 25-hydroxyvitamin-D levels, urinary calcium and deoxypyridinoline excretion were measured. All patients underwent a rehabilitation program including range of motion and progressive resistance exercises, upper body ergometry exercises, standing training with long leg orthosis, wheelchair ambulation or walking either by orthosis or walking aids five times/week during hospitalization. Results: There was no difference between the groups regarding BMD values and Z-scores. Mean serum calcium and parathyroid hormone levels were lower (p=0.016 and p<0.001, respectively), serum phosphorus and alkaline phosphatase levels were higher (p<0.001 and p=0.049, respectively) in the paraplegics as compared to the controls. Positive correlations were found between the radius BMD values and total duration of upper body ergometry exercise (r=0.550, p=0.027) and wheelchair use (r=0.622, p=0.010) and also between the femur BMD values and total duration of therapeutic standing (r=0.351, p=0.039). There was an inverse relationship between the femur BMD values and total duration of immobilization (r= -0.404, p= 0.033). Conclusion: Early rehabilitation interventions may prevent bone demineralization. Paraplegic patients should be followed and evaluated also in long term for the increased risk of osteoporosis. (From the World of Osteoporosis 2008;14: 57-61)